Religious Values Applied By Women In Kakawin Arjuna Wiwaha - Ni Nengah Selasih (Jayapangus Press, 2022)
Kakawin Arjuna Wiwaha tells of Sang Arjuna's marriage to a female companion who has a woman's role and position. Diah Supraba has an angel who is also implied in Kakawin Arjuna Wiwaha, who have their respective roles and positions that inspire women in the era of globalization. The purpose of this study was to analyze the religious values ​​contained in kakawin arjuna wiwaha that can be applied by women. The method used in this research is descriptive qualitative. The data collection technique in this research is a literature study on Kakawin Arjunawiwāha which consists of 36 pupuh, 354 stanzas and 24 kinds of metres. This Kakawin was written by Mpu Kanwa during the reign of King Airlangga (1019-1042) between 1028 and 1035 AD. This study describes the religious values ​​shown by women in Arjuna Wiwaha's kakawin, namely 1) Purity (sivam), a woman is obliged has purity both physically and spiritually in her like a Goddess. 2) A woman who has a strong patience is Diah Suprabha, ordered by Hyang Indra to investigate the secret of the power of a powerful giant named Niwatakawaca, with full devotion to carry out the task at hand with great patience; 3) Diah Tilotama's love is so great and sincere, it can be seen from the restlessness of her heart seeing her husband who is upset and trying to comfort his husband's heart; 4) The nymphs are verydevoted/ obedient to everything that is ordered by Lord Indra 5) The nymphs (Diah Suprabha) are loyal to the king of heaven, so that all orders are never rejected even though they have to sacrifice their bodies 6) The angel who is most seen making sacrifices is Diah Suprabha who was willing to sacrifice himself to go directly to the enemy from Indraloka who was the most feared, namely Niwatakawaca. Kakawin Arjuna Wiwaha as a guide and learning for women to become strong women.